2004
DOI: 10.1007/s10646-003-4427-y
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Bioassay Integrating Individual and Biochemical Responses Using Small Fish Species

Abstract: The interest in the ecological relevance of risk assessments and, thus, in in situ bioassays has been increasing in the last years. The present study developed a time- and cost-effective in situ bioassay, aiming at obtaining, in a short period of time and with a minimum of resources, a set of ecologically relevant toxicological information in a site-specific approach. Poecilia reticulata and Gambusia holbrooki were chosen as test species. Post-exposure feeding inhibition and the biomarkers acetylcholinesterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 70 publications
3
46
0
2
Order By: Relevance
“…The regression model revealed that the temperature, salinity, and the interaction between salinity and the sediment silt content, prevailing during the 48-h exposure, significantly influenced postexposure feeding. Thus, environmental factors may act as confounding factors during in situ assays and, in the absence of in situ control chambers (as used by other scientists [37,38,[42][43][44][45][46][47][48][49]) and/or of ideal reference sites, regression models such as this one may become valuable tools, confirming the conclusions of other studies that also used regression models to adjust in situ results [9,10,19,32,37,38,45,50].…”
Section: Discussionsupporting
confidence: 60%
“…The regression model revealed that the temperature, salinity, and the interaction between salinity and the sediment silt content, prevailing during the 48-h exposure, significantly influenced postexposure feeding. Thus, environmental factors may act as confounding factors during in situ assays and, in the absence of in situ control chambers (as used by other scientists [37,38,[42][43][44][45][46][47][48][49]) and/or of ideal reference sites, regression models such as this one may become valuable tools, confirming the conclusions of other studies that also used regression models to adjust in situ results [9,10,19,32,37,38,45,50].…”
Section: Discussionsupporting
confidence: 60%
“…Postexposure feeding rate has recently been explored as a sublethal endpoint with great potential for use in situ [15][16][17][18][19]. These assays typically involve exposure of test organisms to a specified quantity of food for a brief period (e.g., 1 h) in the laboratory after a short-term (e.g., 48 h) laboratory or field exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, average temperature during autumn and winter was close to the range indicated as triggering both quiescence in eels and WSS. Furthermore, several important changes compatible to a combined effect of cold and chemical stress were observed in the contaminated estuaries of Lima and Douro Rivers during the autumn and winter: (1) low K and LSI indexes suggesting that lipid storages are decreased in these populations; (2) neurotoxic effects due to AChE inhibition which may impair feeding as found in studies performed with other fish species (Castro et al 2004a); and (3) lower antioxidant capacity increasing the vulnerability of eels to oxidative stressors. Overall, these changes may increase the mortality in the population during cold seasons or increase the accumulation of pollutants in already vulnerable eels.…”
Section: Discussionmentioning
confidence: 79%